PENGARUH INTELLECTUAL CAPITAL, KINERJA LINGKUNGAN DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN - Micco Afdal Yusra; Yunilma Yunilma; Ethika Ethika (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
research aims to examine the effect of intellectual capital, environmental performance and audit committees on financial performance. The population of this research is Manufacturing Company Registered on the Indonesia Stock Exchange for the period 2013-2017. The sampling method uses purposive sampling method. The data used is secondary data with annual reports. Processing data using the IBM SPSS Statistics 21.0 program. The data analysis technique used is Multiple Linear Regression Analysis. The results showed that the Human capital efficiency, Structural capital efficiency, environmental performance and audit committes not influences financial performance. While Capital employed efficiency affected by financial performance.